2007
DOI: 10.1080/00016480600818138
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile nasopharyngeal angiofibromas in Denmark 1981–2003: diagnosis, incidence, and treatment

Abstract: Forty-five male (no female) JNA cases were identified. In 43 cases, clinical data were recovered. Median age was 15 years. The incidence rate in Denmark was 0.4 cases per million inhabitants per year and 3.7 cases per million males (aged 10-24) per year. All patients underwent surgery, and the endoscopic approach was increasingly being used. The embolization procedure proved to be safe and decreased the intraoperative blood loss statistically to 650 ml in the embolized group from an average of 1200 ml in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 23 publications
3
75
1
2
Order By: Relevance
“…71.42% in age group 11-20 & mean age 17.28 y. In the study carried out by Glad H et al, [7], median age was 15 y(range 10-24), whereas in the study carried out by Alfredo Lara Gaillard et al, [8], mean age was 16.8 y (range 9-23 y) which is similar to our results sex distribution: Angiofibroma was found only in males which correlate with literature. In the study carried out by Glad H et al, [7] and Alfredo Lara Gaillard et al, [8], all cases were found in males as in our study.…”
Section: Incidence Of Different Types Of Tumoursmentioning
confidence: 99%
“…71.42% in age group 11-20 & mean age 17.28 y. In the study carried out by Glad H et al, [7], median age was 15 y(range 10-24), whereas in the study carried out by Alfredo Lara Gaillard et al, [8], mean age was 16.8 y (range 9-23 y) which is similar to our results sex distribution: Angiofibroma was found only in males which correlate with literature. In the study carried out by Glad H et al, [7] and Alfredo Lara Gaillard et al, [8], all cases were found in males as in our study.…”
Section: Incidence Of Different Types Of Tumoursmentioning
confidence: 99%
“…discussion JNA is a rare entity with an incidence reported to be approximately 0.4 cases per million, and it predominantly affects adolescent boys. 13 These tumors typically present with epistaxis, nasal obstruction, and a nasopharyngeal mass.…”
Section: Case 1: Ipsilateral Endoscopic Endonasal Approach (Uninostrimentioning
confidence: 99%
“…The most common presentation is unilateral nasal obstruction, followed by epistaxis. 9 Most patients do not have any associated systemic illness. A CT scan and MRI play a critical role in proper evaluation of the tumour.…”
Section: Discussionmentioning
confidence: 99%